Role for Chromatin Remodeling Factor Chd1 in Learning and Memory - Schoberleitner, Ines; Mutti, Anna; Sah, Anupam; Wille, Alexandra; Gimeno-Valiente, Francisco; Piatti, Paolo; Kharitonova, Maria; Torres, Luis; López-Rodas, Gerardo; Liu, Jeffrey J.; Singewald, Nicolas; Schwarzer, Christoph; et al. (Frontiers in Molecular Neuroscience, 2019)
Precise temporal and spatial regulation of gene expression in the brain is a prerequisite for cognitive processes such as learning and memory. Epigenetic mechanisms that modulate the chromatin structure have emerged as important regulators in this context. While posttranslational modification of histones or the modification of DNA bases have been examined in detail in many studies, the role of ATP-dependent chromatin remodeling factors in learning- and memory-associated gene regulation has largely remained obscure. Here we present data that implicate the highly conserved chromatin assembly and remodeling factor Chd1 in memory formation and the control of immediate early gene response in the hippocampus. We used various paradigms to assess short-and long-term memory in mice bearing a mutated Chd1 gene that gives rise to an N-terminally truncated protein. Our data demonstrate that the Chd1 mutation negatively affects long-term object recognition and short- and long-term spatial memory. We found that Chd1 regulates hippocampal expression of the immediate early genes Egr1 and Arc but not cFos and Bdnf, because the Chd1-mutation led to dysregulation of Egr1 and Arc expression in naive mice and in mice analyzed at different stages of object location memory testing. Of note, Chd1 likely regulates Egr1 in a direct manner, because ChIP assays revealed enrichment of Chd1 upon stimulation at the Egr1 genomic locus in the hippocampus and in cultured cells. Together these data support a role for Chd1 as a critical regulator of molecular mechanisms governing memory-related processes, and they show that this function involves the N-terminal serine-rich region of the protein.